Efter Tegnér Experiment med traditionen - Sjödin, Alfred; Svensson, Jimmie (Kriterium, 2018)
Esaias Tegnér (1782-1846) was for a long time considered not only Sweden's foremost poet but also a national symbol, an author who defined the characteristics of Swedish culture. Tegnér's status as the national poet has long since dwindled, and along with it, the attention paid to his work by literary scholars. This volume sets out to prove that the last of these developments should not necessarily flow from the first. Writing in a situation when Tegnér's presence in Swedish culture is much less marked, six younger scholars approach the poems of Tegnér from the angle of their individual research interests to offer fresh readings of one of the most studied oeuvres in Swedish literature. The articles in the first part treat Tegnér's relation to 18th century forms of public poetry, his erotic poems and the question of manuscript culture. In the second part, the central patterns of his poetry in the context of romantic metaphysics are reexamined, as well as his metrical art, in the light of cognitive and semiotic theories. The third part concerns aspects of the Tegnér tradition in Swedish culture: his role as a character in fictional and biographical representations, and the use of his work as raw material by 20th and 21h century poets. Together, the articles demonstrate the lasting interest of Tegnér's works and the need to revisit them from new angles.